Effects of combined physical and cognitive program performed in socially enriched environment on older people’s cognitive abilities and quality of life (StimCoAPS): study protocol for a randomized controlled trial - David Clarys; Veronique David; Virginie Migeot; Tiphanie Gonnord; Olivier Dupuy; Marion Albouy; Rebeca Grangeiro; Catherine Esnard; Geoffroy Boucard; Pierre Faivre; Soleane Vielotte; Maxime Pilon; et al. (BMJ Open Sport & Exercise Medicine, 2023)
The number of older people worldwide is constantly increasing. However, ageing is accompanied by a decline in cognitive ability that can affect quality of life. Cognitive, physical and social activities can all slow this decline but social factors and their contribution to the well-being remain under-researched. The aim of this study is to analyse how the practice environment can foster these social relations and thus enhance well-being and to identify the psychological dimensions that are activated by social relations. This study is a 3-year randomised controlled trial designed to assess the effects on participants’ cognitive abilities and quality of life of a combined (ie, physical and cognitive) training programme in different social practice environments. A total of 159 older people (≥65 years old) will be recruited and randomly assigned to one of three practice environments: individual practice at home (n=53), group practice in a gymnasium (n=53) and group practice in an enriched environment (n=53). All participants will complete 12-week combined training sessions and will be assessed four times: before the start, in the middle, at the end and 6 months after the end of the programme. They will undergo cognitive function (episodic memory and executive functions), physical capacity (aerobic fitness, muscle strength and dynamic balance) and psychosocial assessments (indicators of psychological well-being, social support, self-esteem, anxiety, depression and achievement goal strategies), as well as semistructured interviews. Statistical analyses will be conducted to assess the effect of the practice environment on the perceived benefits of this programme in terms of cognitive abilities and quality of life, and to determine the role of psychosocial factors in this relationship.This protocol has been approved by an institutional review board (CERSTAPS: IRB00012476-2022-20-01-146). Trials registration number: NCT05721508.